2007
DOI: 10.1080/13561820701585296
|View full text |Cite
|
Sign up to set email alerts
|

Online interprofessional learning: The student experience

Abstract: Health and social care students in a faculty in the United Kingdom learn together in an interprofessional module through online discussion boards. The module assessment encourages engagement with technology and with group members through peer review. An evaluation of student experience of the module gathered data from 48 students participating in 10 online groups. Analysis of contributions to discussion boards, and transcripts of interviews with 20 students revealed differing levels of participation between in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 12 publications
2
46
2
4
Order By: Relevance
“…''On the job'' learning for online facilitators appears to be common (ELF 2006) and we felt it was more feasible for experienced faculty committed to IPE to learn online teaching skills then for experienced online faculty to learn about IPE. Our findings differ somewhat from Miers et al (2007) who found little evidence of analytical and evaluative skills in their online course for health and social science students. From our perspective, the role of the facilitator is essential to foster critical analysis through the use of stimulating and challenging questions and observations (Solomon & King 2010).…”
Section: 1contrasting
confidence: 56%
See 1 more Smart Citation
“…''On the job'' learning for online facilitators appears to be common (ELF 2006) and we felt it was more feasible for experienced faculty committed to IPE to learn online teaching skills then for experienced online faculty to learn about IPE. Our findings differ somewhat from Miers et al (2007) who found little evidence of analytical and evaluative skills in their online course for health and social science students. From our perspective, the role of the facilitator is essential to foster critical analysis through the use of stimulating and challenging questions and observations (Solomon & King 2010).…”
Section: 1contrasting
confidence: 56%
“…They found no differences between student scores on team process between the two formats; however, students who participated in the blended learning situation had more positive perceptions of their interprofessional course achievements. Miers et al (2007) examined student experiences with online interprofessional…”
Section: Introductionmentioning
confidence: 99%
“…Neither student reported feeling any hesitancy in providing their own critiques on colleagues' work (although Student A did report a colleague's distressing response to a critical comment, and learnt how better to frame critiques in future). We had expected more reluctance to criticise other's work, as reported by Miers et al (2007): Students reported benefiting from the peer review process but were uncomfortable with critiquing each other's work. (Miers et al 2007, p529).…”
Section: Discussionmentioning
confidence: 99%
“…While there is, as yet, little evidence that they actually enhance analytical and conceptual skills (Miers, Clarke & Pollard, 2007;Revere & Kovach, 2011), the discussion board has been commended as an integral instrument of e-learning with diverse uses (Harman & Koohang, 2005), as a means of facilitating camaraderie (Farquharson, 2007) and as an archive for fostering mutual accountability (Moule, 2006). For this, the pilot project, staff anxieties that the logistics and practicalities of the venture would run smoothly tended to detract from careful planning about how the discussion board would be used, and for this reason, the discussion board was set up in an 'open' way.…”
Section: Overview Of Discussion Board Activitymentioning
confidence: 99%